Effect of Interaction between Earthworm and Microbes on the Degradation Time of Agro-Waste - Emenike, Chijioke Uche; Hamid, Fauziah Shahul; Agamuthu, Periatamby (Applied Mechanics and Materials, 2013)
Impact of macro-organisms in biological processes had been considerably studied but some of the discrete interactions that exist between macro- and micro-organisms still remain complex and sometimes elusive. Agro-waste is a type of waste that remains highly inevitable in our society and its disposal is a subject of concern. Therefore, this study aimed to degrade sugarcane bagasse which is a significant agro-waste in Malaysia, while trying to understand the interaction between microbes and earthworm utilized in the bioprocess. Sugarcane bagasse was blended with spent tea in equal ratio before composting with the aid of Eudrilus eugeniae and introduced microbial consortia. Though varied, pH values across the amendments tended towards alkaline state, just as the available Phosphorus (P) and exchangeable Potassium (K) increased in the value. Total organic carbon (TOC) across the amendments showed reduction in value; 47% in TS (tea and sugarcane bagasse), whereas 25% in TS6M (Tea + sugarcane bagasse + 6 microbes) and 68% in TS3M (tea bagasse + 3 microbes). However, weight loss in Eudrilus eugeinae was found to be proportional to the reduced time of degradation. TS3M at 33% worm weight loss was recorded at 11 day degradation time, than TS6M (27%) and TS (16%) that showed 13 and 20 days degradation time respectively. Weight loss in earthworm is correlated with microbial interaction and can be a reflection of rate decomposition of organic components of agro-waste in a vermicomposting process.